Conservative thinkers the key contributors to the political thought of the modern Conservative Party - Garnett, Mark 1963-; Hickson, Kevin (Manchester Univ. Press, 2009)
Includes chapters on Harold Macmillan; Rab Butler and the One Nation Group; Quintin Hogg, Lord Hailsham; Enoch Powell; Angus Maude; Keith Joseph; the Traditionalists; Ian Gilmour and the Wets; John Redwood; and David Willettts